Metabolic and Hepatic Effects of Empagliflozin on Nonalcoholic Fatty Liver Mice [Corrigendum] - Niu S; Ren Q; Chen S; Pan X; Yue L; Chen X; Li Z; Zhen R (Diabetes, Metabolic Syndrome and Obesity, 2023)
Niu S, Ren Q, Chen S, et al. Diabetes Metab Syndr Obes. 2023;16:2549–2560. The authors have advised the correspondence section on page 2549 is incorrect. The correct correspondence details are as follows. Correspondence: Shuchun Chen, Department of Endocrinology, Hebei General Hospital, Shijiazhuang, Hebei, People’s Republic of China, Email chenshuc2014@163.com The authors apologize for this error.